Talking at cross-purposes : the dynamics of miscommunication - Tzanne, Angeliki (Pragmatics & beyond, 2000)
Misunderstandings have been examined extensively in studies on cross-cultural (mis)communication which associate them with participants' differing cultural backgrounds and/or linguistic knowledge. Drawing on a large corpus of misunderstandings from cross- and intra-cultural encounters, this book argues that miscommunication does not relate exclusively to participants' background differences or similarities, but that its creation and development are tightly interwoven with the dynamic manner in which social encounters unfold. Against a backdrop of Pragmatics, Conversation Analysis and Goffman's.